AFRICAN ORATURES AND VADAKKANPATTU: CONFLUENCE OF STORIES AND HISTORY - Abraham, Jyothi Susan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
People have an insatiable desire for stories about their own lives and the world around them, both living and non-living. Wars are often waged to honour their bravery, celebrate their accomplishments, and ensure their legacy endures. This paper analyses the early forms of historical representations from Africa and South India. Griots of Africa served the purpose of conserving the consciousness of the tribe and the death of a griot was mourned as if a library has burned down. Vadakkanpattu narrated the cultural history, legality, and social structure of certain regions of Kerala. These songs were popularised through movies and stories of the bygone days and continued to get preserved in the form of memory imprinted in the psyche of the people through their exaggerated visual representation on the silver screen. Postcolonial vindication of precolonial existence draws upon the oral traditions of the land for validation. Colonial interventions disrupt the linear flow of history, casing distortions, rerouting, and erasures. These can be understood by viewing written history as an extension or continuation of the original oral traditions.